Integrating Financial Literacy and Business Planning in Higher Education: Evidence from PKM-Based Learning Programs - Sentosa, Bambang Mardi; Suherman, Agus; Firdaus, M. Yus; Rianto, Joko; Kurniawan, Andri; Putri, Walla Astianty; Novitri, Bella Suci; Murodi, Ahmad; Muhtadi, TB. Yudi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of financial literacy and business planning skills in higher education is essential to prepare students for the challenges of the modern economic landscape. This study examines the effectiveness of incorporating financial literacy concepts into business planning through the implementation of Programs to the Community (PKM)-based learning. Employing a mixed-methods approach, quantitative data were collected through pre- and post-tests measuring students’ knowledge and skills, while qualitative insights were obtained from focus group discussions and reflective journals. The participants consisted of 20 undergraduate students from various disciplines in Indonesian universities, engaged in PKM projects over one academic semester. Findings indicate a significant improvement in students’ ability to develop comprehensive business plans, manage budgets, and evaluate financial feasibility, with an average knowledge increase of 28% compared to baseline. Qualitative data reveal that PKM-based learning fosters critical thinking, collaboration, and entrepreneurial mindset, while contextualizing theoretical knowledge into practical applications. The study concludes that integrating financial literacy into PKM-oriented business planning courses provides a holistic and experiential learning model, contributing to students’ readiness for professional and entrepreneurial endeavors. These results highlight the potential for scalable implementation of PKM-based curricula in higher education to strengthen economic empowerment and innovation capacity among graduates.